Legionella-Associated Lung Abscess: Critical Pathogen or Minor Isolate? - Gordon CK Dow; Anthony W Chow (Canadian Journal of Infectious Diseases)
Two cases of lung abscess, in which Legionella species were identified in association with other bacterial isolates, are presented. In the first case, Legionella pneumophila and Klebsiella pneumoniae were identified in a 24-year-old post renal transplant patient with a right upper lobe pulmonary abscess. Healing did not occur until the institution of specific therapy directed against legionella. In the second case, Legionella micdadei and several other respiratory bacterial pathogens were identified in a 74-year-old woman with a lung abscess. The patient later died with multisystem failure despite adequate antimicrobial therapy. Prior cases of legionella-associated lung abscess have occurred predominantly in corticosteroid-treated patients. The role of coexisting bacterial isolates remains obscure.